2008
DOI: 10.1055/s-2008-1078718
|View full text |Cite
|
Sign up to set email alerts
|

Progesterone is Extensively Metabolized in Osteoblasts: Implications for Progesterone Action on Bone

Abstract: The effect of progestogens on bone is controversial with some studies suggesting an anabolic action while others show no effect. Prereceptor metabolism via localized expression of specific enzymes may have major impact on progesterone action in bone and may explain some of the discrepancies between studies. We therefore investigated the metabolism of progesterone in primary cultures of human osteoblasts and MG-63 osteoblastic cells. Osteoblasts and MG-63 cells were incubated with 4- (14)C-progesterone tracer a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 25 publications
0
3
1
Order By: Relevance
“…Progesterone promotes osteocalcin gene transcription by stimulating the expression of c-fos and c-jun, resulting in osteoblast proliferation and differentiation [20]. Depending on their osteoblastic commitment, osteosarcoma cell lines respond to sex steroids [34]. In contrast to our findings and the results of studies supporting the inhibitory effects of progesterone on the proliferation and development of bone cells, there are reports suggesting that progesterone signaling is not essential for bone growth and turnover [19].…”
Section: Discussioncontrasting
confidence: 70%
“…Progesterone promotes osteocalcin gene transcription by stimulating the expression of c-fos and c-jun, resulting in osteoblast proliferation and differentiation [20]. Depending on their osteoblastic commitment, osteosarcoma cell lines respond to sex steroids [34]. In contrast to our findings and the results of studies supporting the inhibitory effects of progesterone on the proliferation and development of bone cells, there are reports suggesting that progesterone signaling is not essential for bone growth and turnover [19].…”
Section: Discussioncontrasting
confidence: 70%
“…Osteoblasts (292) and osteoclasts (369) express both PR-A and PR-B (550), suggesting that progesterone may exert its actions on both types of bone cells. Some in vitro studies showed that progesterone can be metabolized by osteoblasts (388) and that progesterone bounded PR exerts its anti-apoptotic action on osteoblast through inhibiting the activations of caspase-9 and -3 (514). Recent studies using conventional PR knockout (PRKO) mice (289) reported that PRKO mutants exhibited high bone mass with increased bone formation and reduced osteoclast surfaces (398).…”
Section: Progesterone Receptorsmentioning
confidence: 98%
“…AKR1C1 mRNA expression is highest in the lung, followed by the liver, testis, mammary gland, endometrium and brain. Recent reports show the expression of AKR1C1 in the kidney [8], adipose cells [9], skin [10], osteoblasts [11] and optic nerve head astrocytes [12]. Among the isoforms, AKR1C1 most efficiently reduces biologically active progesterone and 5␣-pregnan-3␣-ol-20-one into their corresponding 20␣-hydroxysteroids [7,13,14].…”
Section: Introductionmentioning
confidence: 98%